Pantawid Pamilyang Pilipino Program (4P’s) and the Academic Performance of Pupil-Beneficiaries - Celestra, Dhona (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study investigated the impact of the Pantawid Pamilyang Pilipino Program (4Ps) on the academic performance of pupil-beneficiaries in selected public elementary schools in Baras District during the School Year 2025–2026. The schools included Baras Elementary School, Baras-Pinugay Elementary School (Main), Baras-Pinugay Elementary School (Phase 2), Evangelista Elementary School, and Santiago Elementary School. A total of 355 pupil-beneficiaries served as respondents, described in terms of age, sex, grade level, sibling position, number of children in the family, monthly family income, parents’ educational attainment, and parents’ occupation. The study employed a descriptive survey research design, using a researcher-made questionnaire-checklist to determine the extent of the program’s impact on attendance and school participation, motivation and study habits, availability of educational resources, and parental involvement and support. Documentary analysis of pupils’ first-quarter grades was also conducted to assess academic performance. Findings revealed that most respondents were 11 years old, female, third-born, from families with five to six members and monthly income below Php 10,000. Fathers were predominantly manual laborers, while mothers were generally unemployed, with parents’ education ranging from college undergraduates to graduates. The 4Ps often impacted pupils’ attendance, motivation, study habits, availability of educational resources, and parental involvement as perceived by the pupils. No significant differences were observed based on sex, grade level, parents’ educational attainment, occupation, or family income; however, age, sibling position, and number of children in the family showed significant influence on specific variables. Pupils’ academic performance was satisfactory. A significant relationship existed between attendance and school participation and academic performance, while other variables showed no correlation. The study recommends enhanced monitoring, study skills workshops, provision of learning resources, parental engagement programs, and structured guidance tailored to pupils’ age and maturity to optimize the benefits of the 4Ps.
Keywords: Pantawid Pamilyang Pilipino Program, academic performance, pupil-beneficiaries, attendance, motivation, educational resources, parental involvement